Decreasing anthropogenic pressure on soil microflora by using capsulated fertilizers - Tymchuk, Ivan; Malovanyy, Myroslav; Holets, Nataliya (Lviv Politechnic Publishing House, 2017)
This article focuses on finding ways to preserve soil fertility. At the present time, in conditions of intensive farming, do not pay attention to such an important part of the agricultural ecosystem as soil microflora. An impact on the number of total and nitrogen-fixing microorganisms of the soil at bringing different types of fertilizers on the most common types of soil of Lviv region are determined.
Keywords: soil microflora; capsulated fertilizer